Self-Reported Negative Influence of Gambling Advertising in a Swedish Population-Based Sample - Binde, Per (J Gambl Stud, 2018)
This study investigated the negative influence of gambling advertising, that is, gambling more often or for more money than intended. We analyzed data from wave four of the Swedish Longitudinal Gambling Study (Swelogs), in which the self-perceived negative influence of gambling advertising was measured by responses to three survey questions. Few gamblers reported having been negatively influenced by gambling advertising. Among those who reported such influence, problem gamblers were overrepresented. Those who had set limits for their gambling reported a negative influence from advertising more often than others, which likely was caused by a perception that advertising is detrimental to efforts to cut down on excessive gambling. A multivariate regression analysis showed that negative influence from gambling advertising was positively associated with problem gambling, gambling at least monthly, participation in online gambling, and being in the age group 30–49 years. We conclude that although few gamblers are negatively influenced by gambling advertising, the adverse effects on those that are should not be neglected. For a considerable number of people, gambling advertising substantially contributes to problem gambling.